PENYELESAIAN SENGKETA BISNIS MELALUI ALTERNATIVE DISPUTE RESOLUTION (ADR) - Joko Nur Sariono; Agus Dono Wibawanto (Perspektif, 2006)
ADR represent alternative of solving of extrajudical done law dispute that is passing process of negonisasi and of mediasi and of abitrase for the process of and negonisasi of mediasi represent process of is solving of dispute compromisely with result of troubleshooting with while abitrasi represent process of solving of dispute by compromise of negonisasi compete which decision have the character of final.